Self Determination in Nicola Yoon’S Novel Everything, Everything - Wulan, Sri; ., Asnani; Hariani, Safitri; Pratiwy, Devi; ., Pardi (KnE Social Sciences, 2019)
This paper focuses on the analysis of self-determination. The main theory of selfdetermination applied is that developed by Ryan and Deci and the supporting theory is adopted from Wehmayer. In the data analysis, this study uses descriptive qualitative method. By using this SDT (Self Determination Theory), two points are discussed. First, it is self-determined motivation found in the novel. Further, there are two types of the protagonist’s determined motivation which are found in the novel. Autonomous (Intrinsic) motivation comes from the person’s own mind. The protagonist has her own thought to determine her life and her choice. Meanwhile, controlled (extrinsic) motivation is caused by the presence of external influences from the results of interacting with other characters in the novel. Both types of motivation encourage the protagonist to believe what she will do and choose for her life. The second point in discussion is the protagonist’s life choices. Even though she is assumed to suffer from SCID (Severe Combined Immunodeficiency Disease), and she is considered to have a disability, she dares to make decisions that could endanger herself. However, she finally proves that the self-determination done by the protagonist in Yoon’s novel Everything, Everything is in accordance with what she wants. At last, she feels alive. Keywords: Self determination, motivation, intrinsic motivation, autonomous motivation